Human defensive behaviors to threat scenarios show parallels to fear- and anxiety-related defense patterns of non-human mammals - Caroline Blanchard, D; Hynd, April L; Minke, Karl A; Minemoto, Tiffanie; Blanchard, Robert J (Neuroscience and biobehavioral reviews, 2001)
Defense patterns of rats and mice have been characterized in terms of the relationships between the type of defensive behavior (e.g. flight, freezing, hiding, defensive threat/attack, and risk assessment) and particular features of the eliciting (threat) stimulus and the situation in which it is encountered. Because the defense systems of rodents serve as major models for investigating and understanding both the physiology and the behavioral expression of emotional response to aversive stimuli, it is essential to evaluate whether these systems show strong parallels in human responsivity to threat. One hundred and sixty male and female undergraduate students read a set of 12 scenarios involving a present or potential threatening conspecific, and chose a primary defensive response to each. These scenarios were designed to vary features known to influence defensive responding in rodents: magnitude of threat; escapability of the situation; ambiguity of the threat stimulus; distance between the threat and the subject; presence of a hiding place. Male and female responses to the various scenarios were highly correlated, except for yell, scream, or call for help which was frequent for females, rare for males. However, a combination of this response category with 'attack' showed a highly positive (+0.96) male-female correlation, across scenarios.Correlations between manipulated (and rated) features of the threat stimulus and situation, and type of defensive behavior chosen, strongly supported a view that the patterning of defensive behavior is similar for humans and non-human mammals. Significant correlations were obtained relevant to eight specific hypotheses derived from the animal literature, with some support for two additional hypotheses (non-significant correlations averaging 0.4 or more in expected direction). While three predicted correlations were not supported in these findings, only a single significant correlation was obtained that had not been predicted on the basis of the animal literature. Although the scenario approach, and this application, have specific limitations, these results provide substantial suggestion of congruence between human and non-human mammal defense systems.